Body composition in predialysis patients on a low protein diet supplemented with ketoanalogues of essential aminoacids versus a free diet - Shutov Evgeny; Fedorov Dmitryi (The Korean Society of Nephrology, 2012)
More than a half of patients starting dialysis are found to have a poor predialysis nutritional status. A low-protein diet (LPD) delays CKD progression but occasionally lead to some changes in body composition and malnutrition. We performed a prospective, open-label, parallel, randomized and controlled trial to compare a body composition and biochemical parameters of CKD patients who were on LPD supplemented with ketoanalogues of essential aminoacids (KA) with those on a free diet (FD). Biochemical and bioimpedance parameters were analyzed in CKD patients every month before initiation of dialysis. Impedance measurements were performed with a multifrequency bioelectrical impedance analyzer. Group I (n=14 patients, 8 male, 6 female; 53 ±12 y.o; glomerular filtration rate (GFR) 18,8 ± 6,3 ml/min (MDRD formula) ) having LPD (0.5 g/kg/day protein) supplemented with KA (1 tablet/5 kg of body weight a day) was compared with matched Group II on FD (n=15 CKD patients with GFR 17,8±5,9 ml/min). Protein intake was lower in patients on LPD (0,5±0,1 g/kg/day protein) than on FD (1,14±0,21g/kg/day; p<0.0001). The declining slopes of GFR during LPD + KA period were significantly lower than those during FD, so Group I was invited to dialysis later - after 32,4±12,7 months in contrast with Group II in 14,5± 7,7 months (p‹0,0001). Albumin and pre-albumin levels remained stable in Group I, but they decreased in Group II (Δ=-0,93±0,21 g/l, Δ=-0,15±0,12g/l respectively; p<0.001) at the start of dialysis. The body composition didn't change significantly in patients on LPD while in patients on FD their lean body mass decreased by 3,5±2,3 kg (p‹0,001), body fat mass declined by 1,5±04kg (p‹0,01),simultaneously extracellular water increased +1,5±0,9l, p‹0,05. In conclusion, LPD and KA delayed CKD progression without nutritional status and body composition deterioration in contrast to FD. Controlled LPD with KA should be widely recommended as a safer dietary method for pre-dialysis CKD patients than FD.